The modern clinical and epidemiological characteristic of opisthorchosis in Sumy region - N. D. Chemych; N. I. Iliyna; V. V. Zakhlebaeva; S. E. Sholochova; A. V. Kochetkov (Журнал инфектологии, 2014)
The analysis of epidemiological situation with opisthorchosis in Ukraine and North-Easten region was conducted. The clinical course of disease in endemic centre was researched. Peculiarity is a high percentage of latent form. The clinic and laboratory signs of disease were formed.